Dark Portrait of Domestic Violence: A Case Study of Domestic Violence Victims in Binjai, North Sumatra - Ningsih, Dewi Melia; Anggraini, Dinda; Hartini, Hartini; Khairunnisa, Khairunnisa; Marlina, Marlina; Sarah, Sase Annaina; Andrayani, Shela; Suzanna, Ella (Program Studi Psikologi Fakultas Kedokteran Universitas Malikussaleh, 2024)
Domestic violence (DV) against women is a form of abuse that has severe physical and psychological consequences for victims. This study aims to explore the experiences of DV victims in Binjai, North Sumatra, and the psychological and physical impacts they endure. The research employs a qualitative approach with a case study method. The subject of this study is a female DV victim who shared her experiences of violence inflicted by her husband, resulting in physical, psychological, and social changes in her daily life. The findings indicate that the victim suffers from psychological trauma, including anxiety, fear, and sleep disturbances, as well as physical effects such as bruises and hair loss. The violence also leads to decreased social interaction, causing the victim to become isolated from her surroundings. This study highlights the importance of women's empowerment, social support, and medical assistance for DV victims, as well as the need for intervention from authorities and relevant institutions to protect women's rights. The study's implications emphasize the necessity of both preventive and curative measures against DV cases and greater attention to women's protection within households.